Buprenorphine for Cancer Pain in Patients With Nonmedical Opioid Use: A Retrospective Study at a Comprehensive Cancer Center. (May 2020) - Hansen, Eric; Nadagoundla, Chitra; Wang, Chong; Miller, Austin; Case, Amy Allen
Background: Outpatients with cancer commonly have nonmedical opioid use (NMOU) behaviors and use opioids to dull emotional and existential suffering. Buprenorphine is often used for cancer pain due to less reported euphoria when compared to other opioids. Methods: A retrospective review was done in patients who were prescribed buprenorphine for cancer pain. Pain scores were reported on a Likert pain scale of 1 to 10. Nonmedical opioid use was defined as patients taking opioids for emotional pain at or above the maximum prescribed amount. Results: For 16 patients, the mean pain score prior to buprenorphine (pain pre) was 8.3 (Standard deviation (Std) 1.6), and the mean pain score on follow-up post-buprenorphine (pain post) was 6.1 (Std 2.3) with a reduction in mean pain score (pain change) of −2.0 (Std 2.9, P = .059). Those patients without NMOU had a pain prescore of 9.5 (Std 1.0) and pain post of 4.3 (Std 2.5) with a mean pain change of −5.0 (Std 1.7, P = .20). The mean pain change in those with chemical coping (−1.3/Std 2.7), illicit drug use (−2.8/Std 1.0), or psychiatric comorbidity (−2.4/Std 2.7) were reduced after buprenorphine, however, not statistically significant. Outpatient rotation to buprenorphine was well tolerated. Conclusions: The pain score in those patients without NMOU was significantly lower after rotation to buprenorphine than those with NMOU. We deduce that in those with NMOU, it is more challenging to achieve pain relief with buprenorphine. Overall, for all patients, rotation to buprenorphine resulted in a marginally significantly reduced pain score.